Manajemen Biaya dan Waktu Pelaksanaan Proyek Pembangunan Co-Working Space Kabupaten Lamongan - Hepiyanto, Rasio; Dhana, Rio Rahma; Febrianto, Andreyas Dian (Jurnal Talenta Sipil, 2025)
In construction projects, particularly in the development of the Co-Working Space in Lamongan Regency, discrepancies between the planned schedule and actual outcomes often occur, both in terms of time and cost. This is generally caused by ineffective planning and control during project execution. This study aims to analyze cost and time management of the project to achieve more efficient and timely implementation. The research method applies the Critical Path Method (CPM) as the primary approach to determine the critical path and minimum project duration, complemented by the Program Evaluation and Review Technique (PERT) to estimate time uncertainties. The results show that using CPM, the critical path involves activities A, B, D, F, G, E, V, X, AA, AB, AD, AE, AG, AK, AT, BA, AU, AV, AY, BB, BD, AZ, BH, and BE with a total duration of 136 days, saving 22 days from the initial plan of 158 days. Using PERT with the same critical path, the project is estimated to be completed in 148 days, saving 10 days, with a cumulative distribution value of 3.7, indicating a 99.98% probability of project completion before the target date. In conclusion, CPM and PERT are effective for controlling project cost and time, with CPM providing greater time efficiency.